Advancing Renewable Energy: The Prospects of Hydrothermal Liquefaction (HTL) for Biomass into Bio-oil Conversion - Gronwald, Frank; Wang, Lijung (International Journal of Environment, Engineering and Education, 2024)
Hydrothermal liquefaction (HTL) offers a promising approach to convert biomass into bio-oil, contributing to sustainable energy solutions and reducing dependence on fossil fuels. HTL mimics natural geological processes by decomposing biomass at high temperatures (200–350°C) and pressures (10–25 MPa) in a water-based environment, producing bio-oil that can be refined for various energy applications. Despite its potential, several technical challenges limit the efficiency and scalability of HTL. The high energy requirements for maintaining these conditions also pose economic challenges, making HTL less competitive against traditional energy sources. HTL is the complex composition of bio-oil, which contains a mix of organic compounds that make refining and upgrading challenging. This complexity also affects bio-oil’s stability, requiring advanced purification techniques to ensure quality and usability. Solid residue formation during HTL reduces bio-oil yields and increases processing costs. Recent advances aim to address these limitations. New catalysts, such as metal oxides, improve bio-oil yield and reduce oxygen content, enhancing fuel quality. Innovations in reactor design, including continuous flow and microwave-assisted reactors, improve heat transfer and operational stability. Integrating HTL with other biomass conversion technologies, like anaerobic digestion, also offers pathways to increase efficiency and energy recovery. Advances in analytical techniques, like gas chromatography and mass spectrometry, are also improving bio-oil characterization, informing more effective upgrading strategies. While challenges remain, ongoing research in catalyst development, reactor optimization, and process integration strengthens HTL’s potential as a sustainable energy solution, supporting its role in advancing bio-oil production for a cleaner, renewable future.